Trochlear Nerve Repair during Retrosigmoid Suprameatal Approach for Petrotentorial Meningioma: Operative Video - Matsushima, Ken; Kohno, Michihiro; Nakajima, Nobuyuki; Ichimasu, Norio (Journal of Neurological Surgery Part B: Skull Base, 2018)
When operating on difficult skull base lesions, it is essential to be able to handle unexpected intraoperative findings or troubles, while achieving maximal lesion removal and minimal functional deficit. This video demonstrates a case of trochlear nerve repair that was performed during the retrosigmoid suprameatal approach for treatment of a petrotentorial meningioma, extending into the Meckel's cave. The patient is a 47-year-old woman with a right petrotentorial meningioma, extending into the Meckel's cave. The retrosigmoid suprameatal approach was performed with preservation of the superior petrosal vein. However, a divided trochlear nerve was incidentally found during tumor resection. We hence carefully dissected both nerve ends from the tumor without shortening their lengths, and repaired them by end-to-end anastomosis, using fibrin glue without any graft materials. The tumor was removed completely and the patient's preoperative facial sensory impairment disappeared after the surgery. The patient's facial sensory impairment disappeared completely, but she had transient diplopia after the surgery. However, the newly developed diplopia resolved completely, and she had no neurological deficits or tumor recurrence during the follow-up period of 1-year.The link to the video can be found at: https://youtu.be/g-B-w_zDudg.
Keywords: cerebellopontine angle; cranial nerve anastomosis; nerve reconstruction; nerve regeneration; skull base surgery